Diagnostic performance of different cholangioscopes in patients with biliary strictures: a systematic review - Kulpatcharapong, Santi; Pittayanon, Rapat; J. Kerr, Stephen; Rerknimitr, Rungsun (Endoscopy, 2020)
Background Cholangioscopy provides direct intraductual imaging, which can enhance diagnostic efficacy during endoscopic retrograde cholangiopancreatography in patients with biliary strictures. This study aimed to review the diagnostic yield of different cholangioscopes for the diagnosis of malignant biliary stricture (MBS).Methods A comprehensive literature review was performed. Full papers of prospective studies using any type of peroral cholangioscope (POC) were included without language restriction. The primary outcomes were sensitivity, specificity, and accuracy of various POCs to diagnose MBS.Results Data from 20 published articles, involving 1141 patients, were extracted. Overall sensitivities of POCs for diagnosing MBS were higher for the diagnosis made under visual impression compared with those from cholangioscopy-guided biopsy (67 % – 100 % vs. 38 % – 100 %), whereas the overall specificities were generally high and comparable (73 % – 100 % vs. 75 % – 100 %). Newer video cholangioscopes (digital single-operator POC [digital SOC], direct POC) with the exception of video dual-operator mother – baby POC (video DOC), provided better sensitivity of cholangioscopy-guided biopsy compared with fiberoptic scopes (digital SOC 80 % – 85 %, direct POC 80 % – 100 %, video DOC 38 % – 100 %, and fiberoptic SOC 49 % – 100 %, respectively). Among these video cholangioscopes, the digital SOC provided the highest technical success rate, at 100 %.Conclusions POCs enhanced the diagnostic yield for diagnosis of MBS. Compared with fiberoptic POCs that only provide good image impression, the digital SOC and direct POC were good at both image impression and cholangioscopy-guided biopsy to diagnose MBS. To ensure high technical success for MBS diagnosis, the digital SOC is a good option.